Dereplication of microbial metabolites through database search of mass spectra - Hosein Mohimani (Nature Portfolio, 2018)
New natural products can be identified via mass spectrometry by excluding all known ones from the analysis, a process called dereplication. Here, the authors extend a previously published dereplication algorithm to different classes of secondary metabolites.